Extent of FLAIR Hyperintense Vessels May Modify Treatment Effect of Thrombolysis: A Post hoc Analysis of the WAKE-UP Trial - Grosch, Anne Sophie; Kufner, Anna; Boutitie, Florent; Cheng, Bastian; Ebinger, Martin; Endres, Matthias; Fiebach, Jochen B.; Fiehler, Jens; Königsberg, Alina; Lemmens, Robin; Muir, Keith W.; Nighoghossian, Norbert; et al. (Frontiers in Neurology, 2021)
Background and aims: FLAIR hyperintense vessels (FHV) on MRI are a radiological marker of vessel occlusion and indirect sign of collateral circulation. However, the clinical relevance is uncertain. We explored whether the extent of FHV are associated with outcome and how FHV modify treatment effect of thrombolysis in a subgroup of patients with confirmed unilateral vessel occlusion from the randomized controlled WAKE-UP trial. Methods: 165 patients were analyzed. Two blinded raters independently assessed the presence and extent of FHV (defined as the number of slices with visible FHV multiplied by FLAIR slice thickness). Patients were then separated into two groups to distinguish between few and extensive FHV (dichotomization at the median <30 or ≥30). Results: 85% of all patients (n=140) and 95% of MCA-occlusion patients (n=127) showed FHV at baseline. Between MCA-occlusion patients with few and extensive FHV, no differences were identified in relative lesion growth (p=0.971), short-term (follow-up NIHSS; p=0.342) or long-term functional recovery (mRS<2 at 90 days post-stroke; p=0.607). In linear regression analysis, baseline extent of FHV (defined as a continuous variable) was highly associated with volume of hypoperfused tissue (β=2.161; 95% CI 0.96-3.36; p=0.001). In multivariable regression analysis adjusted for treatment group, stroke severity, lesion volume, occlusion site, and recanalization, FHV did not modify functional recovery. However, in patients with few FHV, the odds for good functional outcome (mRS) were increased in rtPA patients as compared to placebo (OR=5.3; 95%CI 1.2-24.0), whereas no apparent benefit was observed in patients with extensive FHV (OR=1.1; 95%CI 0.3–3.8), p-value for interaction was 0.11. Conclusion: While the extent of FHV on baseline did not alter the evolution of stroke in terms of lesion progression or functional recovery, it may modify treatment effect and should therefore be considered relevant additional information in those patients who are eligible for intravenous thrombolysis.